Health and economic benefits of single-dose HPV vaccination in a Gavi-eligible country. Issue 32 (6th August 2018) - Burger, Emily A.; Campos, Nicole G.; Sy, Stephen; Regan, Catherine; Kim, Jane J.
Highlights: One-dose HPV vaccination was cost-saving compared to no vaccination. One-dose optimistically averted 19% fewer cases than two-dose vaccination. Two-dose vaccination was generally preferred to one-dose vaccination. One-dose was cost-effective only when accompanied by higher coverage and lifelong protection. Abstract: Background: Although guidelines for prophylactic human papillomavirus (HPV) vaccination recommend two doses for girls ages 9–14 years, several studies have demonstrated similar protection with one dose. Our objective was to evaluate the long-term health and economic impacts of routine one-dose HPV vaccination compared to (1) no vaccination and (2) two-dose HPV vaccination in a low-income country. Methods: We used a three-tiered hybrid modeling approach that captured HPV transmission, cervical carcinogenesis, and population demographics to project long-term health and economic outcomes associated with one-dose HPV vaccination (assuming 80% efficacy against HPV-16/18 infections under three waning scenarios) and two-dose HPV vaccination (assuming 100% efficacy over the lifetime) in Uganda. Costs included the vaccine program (dosage and delivery) costs over a 10-year period and cervical cancer costs over the lifetimes of the current population of Ugandan women. Health outcomes included number of cervical cancer cases and disability-adjusted life years (DALYs). Incremental cost-effectiveness ratios (i.e., cost per DALY averted) were calculated and compared against the Ugandan per-capita gross domestic product. Results: Routine one-dose HPV vaccination of 9-year-old girls required substantial upfront investment but was cost-saving compared to no vaccination when accounting for the cost-offsets from future cancers averted. Forty years after initiating routine vaccination and depending on assumptions of vaccine waning, one-dose HPV vaccination with equivalent coverage (70%) averted 15–16% of cervical cancer cases versus 21% with two-dose vaccination but required only half the upfront economic investment. Vaccination with two doses had an attractive cost-effectiveness profile except if one-dose vaccination enabled higher coverage (90% vs. 70%) and did not wane. Conclusions: One-dose HPV vaccination resulted in cost-savings compared to no vaccination and could be cost-effective compared to two-dose vaccination if protection is longstanding and higher coverage can be achieved.